Hungarian Monitoring, 4 March 1988 . [Magyar rádiófigyelő], 1988. március 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Socialist foreign ministers' meeting in Havana - NATO summit in Brussels - Disturbances in Azerbaijan Domestic Affairs: - Károly Grósz 's meeting with the Afghan deputy Premier - Péter Várkonyi's visit to Bangkok - National Council of Trade Unions (SZOT) and the Party Economy: - Prices, inflation - Talks with Suzuki and Fiat Külpolitika: - Szocialista külügyminiszterek havannai értekezlete - Brüsszeli NATO csúcs - Azerbajdzsáni zavargások Belpolitika: - Grósz Károly találkozója az afgán miniszterelnök - Helyettessel - Várkonyi Péter bangkoki látogatása - A SZOT és a párt Gazdaság: - Árak, infláció - Tárgyalások a Suzukival és a Fiat-tal